O Efeito diploma no mercado de trabalho não qualificado: Uma aplicação da função de Mincer para o Brasil - Jayane Freires Ferreira; Andréa Ferreira da Silva; José Alexandre Queiroga do Nascimento; Pedro Willame Pereira da Silva (Revista de Economia Mackenzie, 2022)
In 2001, 2004, 2007, 2011, and 2015, Brazil provided an expansion in the offer of places for higher education through the programs Student Financing Fund (Fundo de Financiamento Estudantil [Fies]), University for All Program (Progra-ma Universidade para Todos [Prouni]) and Support Program for Restructuring and Expansion Plans of Federal Universities (Programa de Apoio a Planos de Rees truturação e Expansão das Universidades Federais [Reuni]). As a result, this article aims to analyze the effect that this proportion of higher education graduates had on the income of individuals with secondary education. From the microdata of the National Survey by Household Sample (Pesquisa Nacional por Amostra de Domicílio [Pnad]) of the Brazilian Institute of Geography and Statistics (Instituto Brasileiro de Geografia e Estatística [IBGE]) for the years 2001, 2004, 2007, 2011 and 2015, the theoretical and empirical basis of the Mincerian equation was ap-plied in the estimations. The results show that investing in higher education brings high rates of returns for all years studied, while investing up to high school showed in creasingly declining returns, with a negative variation of 87,8% between 2001 and 2015. The differences in income between high school and higher education graduates are possibly correlated to a greater demand for more skilled workers in the labor market.